2016
DOI: 10.1039/c6ra22342g
|View full text |Cite
|
Sign up to set email alerts
|

Organic transistors based on airbrushed small molecule-insulating polymer blends with mobilities exceeding 1 cm2 V−1 s−1

Abstract: High performance organic transistors have been realized via airbrush technique, using small molecule-insulating polymer blends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Indeed, the impact of fabrication techniques on the versatile blend system has been demonstrated a number of times over the years. Examples of fabrication techniques include spray deposition, line printing, air brushing, inkjet printing, dipping processes, vertical flow, blade coating, and off‐center spin coating …”
Section: Molecular Semiconductor/polymer Blendsmentioning
confidence: 99%
“…Indeed, the impact of fabrication techniques on the versatile blend system has been demonstrated a number of times over the years. Examples of fabrication techniques include spray deposition, line printing, air brushing, inkjet printing, dipping processes, vertical flow, blade coating, and off‐center spin coating …”
Section: Molecular Semiconductor/polymer Blendsmentioning
confidence: 99%
“…This approach is especially attractive for low M w semiconductors. [34,37,62] Low viscosity and dewetting are common drawbacks of small molecules during film casting and blending with insulating polymers enhances their film forming properties. [63,64] Dip-coated films of α,ω-dihexylquaterthiophene (DH4T) and diketopyrrolopyrrolesexithiophene (DPP6T) exhibited a significant improvement in film formation and crystallization when blended with a small fraction of PMMA.…”
Section: Blends With Small Molecular Semiconductorsmentioning
confidence: 99%
“…Madec et al 15 studied the effect of molecular weight of polymer binder and binary solvents on film growth and crystallinity of TIPS‐PEN. Furthermore, Kaimakamis et al 27 reported the effect of small molecule‐polymer ratio on device performance. Nevertheless, a mechanistic understanding of the phase separation and small molecule crystallization is needed to guide process optimization 18 .…”
Section: Introductionmentioning
confidence: 99%